The Potential Use of Dynamics Changes of ctDNA and cfDNA in the Perioperative Period to Predict the Recurrence Risk in Early NSCLC - Zhao, Xiaolong; Dai, Fuqiang; Mei, Longyong; Huang, Depei; Shen, Xudong; Zhang, Hushan; She, Xueke; Ma, Zheng (Frontiers in Oncology, 2021)
Background Postoperative circulation tumor DNA (ctDNA) is a promising method to predict the risk of recurrence. However, the amount of ctDNA in patients with early NSCLC is too small. Cell damages caused during the intraoperative period leads to a significant increase in cell free DNA (cfDNA). Whether cfDNA content is restored to the preoperative level within a short time after surgery may indicate the degree of surgical trauma. In this study, dynamic changes of cfDNA combined with ctDNA in the perioperative period of NSCLC were used to explore the possibility of them as a biomarker to indicate the risk of recurrence. Methods NSCLC patients who planned to undergo radical resection were investigated. 10ml of peripheral blood was collected before, during and 7 days after surgery. DNA concentration was measured, and a 23-gene NGS panel was performed to detect gene mutations. All the patients would be followed-up for at least 18 months. Results A total of 7 patients were sampled. The amount of cfDNA before surgery was 36.6 ± 14.7ng, and increased to 127.2 ± 52.2ng during surgery. 7 days after surgery, it dropped to 45.23 ± 9.41ng in 3 patients and rose to 173.7 ± 80.80ng in the remaining 4. Only 1 patient was ctDNA positive after surgery, with decreasing cfDNA, and he was the only one that relapsed and died within 18 months. Conclusion The use of ctDNA to predict the risk of postoperative recurrence of NSCLC is a very valuable method, and it may be more reliable if combined with the dynamic changes of cfDNA. The amounts of cfDNA are raised by the operation, but will be polarized after surgery in 7 days. Postoperative NSCLC patients with positive ctDNA and reduced cfDNA have a higher risk of recurrence.